Role for Internal Auditor to Cope with IT Risks and IT Infrastructure in Jordan Commercial Banks (Global Journal of Management and Business Research, 2015)
This study aims to provide assurance to senior management on the adequacy of the controls to ensure the IT infrastructure was planned, managed and maintained to support efficient operations and analyze risk assessment and know the role of it auditors to deal with risks which threats attain strategic objectives . The study population consists of the internal auditors in Jordan commercial banks . the most resultsAudits can focus on such major IT assets as ERP systems and help management to make rational decisions in investing in IT assets to attractive new customers and make core competences for company , technology infrastructures have continued to grow in size and complexity.